Morphometrics and structural changes of fig (Ficus carica l. var. Ipoh Blue Giant) syconium during growth, maturation and on-tree ripening - Mat Jusoh, Nur Athirah; Phebe, Ding (Elsevier BV, 2023)
There has been almost no research on fig (Ficus carica) syconium growth and ripening in tropical countries. Therefore, a study using the fig variety Ipoh Blue Giant grown in the Malaysian tropical climate was conducted to determine its physico-chemical characteristics and cellular structure during growth and on-tree ripening. The fig bud was tagged, and its development was monitored weekly from the 1st week after bud emergence (WAB) until syconium senescence. Upon observation, the fig took 12 weeks to develop from a tiny bud into a mature syconium, followed by five (5) days of on-tree ripening before senescence. Based on the fruit size (diameter, volume and weight), the fig exhibited a double sigmoid growth curve with a rapid increase in size during the first four (4) weeks of growth and ripening. Based on its physiological characteristics, the fig demonstrated a climacteric respiration pattern with increased carbon dioxide and ethylene emission on day 1 of on-tree ripening. The green colour of the fig syconium gradually disappeared and turned red as it ripened. The pulp firmness increased as WAB progressed but significantly decreased as ripening occurred, although there were no changes in the total pectin content. The soluble solids concentration of the developing fig was stagnant but increased during ripening and aligned with glucose and fructose contents. The titratable acidity of the fig initially increased as WAB progressed but decreased as it ripened, while the fig pH displayed an inverse trend to the titratable acidity. Overall, the changes in the fig’s cellular structure during growth and ripening aligned with its size.